Smart Parking for Smart Cities using IoT - Ratakonda Bhavani; Avvari Pavithra; Rajarao B.; Sreevani Voruganti; Ganapathi Raju N V (E3S Web of Conferences, 2021)
The idea of smart cities has gained immense popularity in real-time, Internet of Things (IoT) is not just about connecting people and about connecting things. Billions of devices will connect to the internet through sensors they talk to each other. Searching for parking is a routine activity for many peoples in the city around the world. There are many solutions some of the existing solutions are inductive loops, image processing at shopping malls, universities, airports, also, the thought behinds advancement of IoT. With this IoT there is numerous wide scope of utilizations in our day by day life, not many of them are keen urban communities, smart waste administration, smart health, brilliant security, and smart industry applications. This paper provides a novel solution for the people to minimize the waiting time and maximize productivity and help to find the space where the vehicles can be left to decrease the traffic in the leaving region. Internet of Things and distributed computing are two unique parts of innovations. IoT is an arrangement of interrelated gadgets and things with unique identifiers associated with the web can speak with one another. The cloud gives everything as administration i. e. pays for what we use. The obstacle sensor senses the obstacle status when the car is being parked in the parking area and status is sent to the cloud. Utilizing the IoT framework it gives the accessible free stopping spaces, Entry and exit likewise gives payment process through RFID card to diminish the bottleneck of the payment procedure and approve at the passage/leave the entrance of the shopping area.